A Tapered Gridded Estimator (TGE) for the multifrequency angular power spectrum (MAPS) and the cosmological H i 21-cm power spectrum - Bharadwaj S.; Pal S.; Choudhuri S.; Dutta P. (My University, 2025)
In this work, we present a new approach to estimate the power spectrum P(k) of redshifted H i 21-cm brightness temperature fluctuations. The MAPS Cl (va, vb) completely quantifies the second-order statistics of the sky signal under the assumption that the signal is statistically homogeneous and isotropic on the sky. Here, we generalize an already existing visibility based estimator for Cl, namely TGE, to develop an estimator for Cl (va, vb). The 21-cm power spectrum is the Fourier transform of Cl (δv) with respect to δv = |va - vb|, and we use this to estimate P(k). Using simulations of 150 MHz GMRT observations, we find that this estimator is able to recover P(k) with an accuracy of 5-20 per cent over a reasonably large k range even when the data in 80 per cent randomly chosen frequency channels are flagged. © 2018 The Author(s) Published by Oxford University Press on behalf of the Royal Astronomical Society.